A Comparison of Students’ Perceptions on Research Methods Pedagogy in Social-Work and Sport Management Courses - Augustine, Gail M.; Aly, Ezzeldin R. (European Scientific Journal, ESJ, 2020)
Educators often grapple with the task of teaching a research method course in a manner that would engage and sustain students’ attention throughout the semester. The pedagogical dilemma, for the most part, is connecting students’ knowledge and attitude to engage in abstract thinking in the research method course appear to be nebulous. The current study aimed to investigate students’ perceptions about ethics, values, social justice, and diversity in the research methods curriculum, which will provide frameworks for pedagogical understanding between groups. An understanding by comparing the perception of students will be useful in learning methodology for teaching research-related material on both graduate and undergraduate levels. Sixty graduate and undergraduate students from Florida A & M University were surveyed to assess their perceptions of ethics, values, social justice, and diversity in three different research method courses. The researchers used the Statistical Package for Social Science (SPSS) to analyze the data and find the outcomes. Data were analyzed using one-way ANOVA to show comparisons between groups in the learning environments with the students in graduate and undergraduate research methods courses. The implications for addressing ethics, values, social justice, and diversity in the research methods were hypothesized.